The Educational’s Roles in Character Embedding for Scouting Members of Racana Dang Tuanku and Bundo Kanduang - Gustia, Reza; Pamungkas, Alim Harun (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
This research is motivated by scouting education in Racana Dang Tuanku dan Bundo Kanduang which is inseparable from the values of character education. Allegedly there are a number of Racana Dang Tuanku dan Bundo Kanduang Scout Members, who are classified as still productive, when they were prospective members, they did not have any practice about scouting education. Therefore the purpose of this study is to describe the role of scouting education in instilling character values for the Racana Dang Tuanku dan Bundo Kanduang Scout Members. This type of research is a quantitative descriptive. The population in this study was Racana Dang Tuanku dan Bundo Kanduang Scout Members in 2020 starting from the 34th generation to the 37th generation, amounting to 80 people. Samples were taken as much as 75%. The number of samples is 60 people. The data collection technique was a questionnaire. Data collection tool in the form of a list of statements. The analysis technique uses the percentage formula. The results of this study can be seen that: (1) The role of scouting education in instilling character values for Racana Dang Tuanku dan Bundo Kanduang Scouts Members is very high in the aspect of comprehension and practice of scout values reaching 61%; (2) The role of scouting education in instilling character values for Racana Dang Tuanku dan Bundo Kanduang Scout Members is very high in the aspect of developing character education based on religious, cultural, environmental-based and self-potential reaching 68%. The suggestions in this study are (1) Racana Dang Tuanku dan Bundo Kanduang should better utilize the existing facilities and infrastructure so that scouting education is always in demand by Scout Members so that with Scouting education it can shape the character of Scout Members as humans who have noble personalities; (2) Always maintain and improve the character values that have been obtained in Racana Dang Tuanku dan Bundo Kanduang, and implemented in daily life.Keywords: Scouting Education, Character Education